Assessment of Leadership Skills Among Nursing Faculty - Rathod, Shashikala; Kale, Milind; Gokhale, Meghana; Gamare, Priyanka (Journal of Neonatal Surgery, 2025)
Background of the Study Leadership is a cornerstone of effective nursing education. Nursing faculty not only impart knowledge but also serve as pivotal leaders who influence curriculum development, mentorship, policy-making, and institutional advancement. As academic leaders, they are responsible for cultivating a learning environment that promotes student engagement, critical thinking, and professional growth. In the contemporary healthcare landscape, the complexity of patient care and the evolving demands of the profession necessitate that nursing educators possess strong leadership competencies. These competencies include communication, emotional intelligence, decision-making, conflict resolution, and the ability to inspire and lead change. The dual role of faculty—as educators and institutional leaders—makes it essential to assess their leadership skills. Strong leadership among faculty promotes interdisciplinary collaboration, enhances faculty-student relationships, drives innovation in teaching methodologies, and supports the development of evidence-based practices. Moreover, faculty leadership directly influences student outcomes, faculty retention, and the overall reputation of nursing programs. Despite its importance, leadership among nursing faculty is often under-assessed and undervalued, leading to gaps in development and performance. Understanding the current status of leadership skills among nursing faculty will help identify areas for professional development and inform strategies to strengthen educational and clinical leadership across institutions.